Airline schedule punctuality management - Al-Haimi, Abdullah A. (Cranfield University, 1991)
Airline schedule punctuality is a complex problem and one of the major concerns of the airline top management. Flight schedule disturbances may occur as delays and/or cancellations. There are many internal and external reasons for delays. These delays may propagate in the aircraft cycles and cause a large schedule disturbance. This may influences passenger satisfaction and airline resources. The objective of this research is to formulate a systematic approach for schedule punctuality which supports management decision making. The punctuality management system is structured to combine all schedule punctuality components, input and output variables. Five models are incorporated in this system. The first model is the disturbance model which generates random delays based on an estimated Lognormal delay distribution function. The delay analysis is carried out from a one year sample of delay statistics in which general, original , reactionary and other delay types are classified. The second model is the recovery model which incorporates the disturbance model with management strategies to determine delay propagation. A PC based simulation model (SKDMOD) is developed as a prototype which integrates disturbance and recovery models using SIMSCRIPT 11.5. 18 management strategies are simulated covering ground times (30, 40 and 50 minutes), maximum delay times to assign spare aircraft (1, 2, 3, 4, 5, and 6 hours) and spare aircraft using part of the domestic network of Saudi Arabia. The third model is the passengers' attitude model which determines the delay impact functions and the maximum passenger revenue loss based on 262 responses from a passenger interview survey. The fourth model is the revenue model which estimates the passengers' revenue loss. The fifth model is the cost model which estimates the extra cost resulting from implementation of the management strategies. All strategies are evaluated to determine the optimum based on profit and profit margin. OPTIM is the optimization program developed to find the optimum strategy(ies). This approach provides a guidelines for the management of punctuality. It integrates all the tools developed in a decision support system framework.